## Results (displaying matches 1-50 of 44190) Next

Label Class Equation Sato-Tate $$\overline{\Q}$$-simple $$\GL_2$$ Rank*
461.a.461.2 461.a $$y^2 + y = x^5 - x^4 - 39x^3 + 10x^2 + 272x - 306$$ $\mathrm{USp}(4)$ 0
587.a.587.1 587.a $$y^2 + (x^3 + x + 1)y = -x^2 - x$$ $\mathrm{USp}(4)$ 1
604.a.9664.1 604.a $$y^2 + (x^2 + x + 1)y = 4x^5 + 9x^4 + 48x^3 - 4x^2 - 53x - 21$$ $\mathrm{USp}(4)$ 0
713.a.713.1 713.a $$y^2 + (x^3 + x + 1)y = -x^5 - x$$ $\mathrm{USp}(4)$ 1
743.a.743.1 743.a $$y^2 + (x^3 + x + 1)y = -x^4 + x^2$$ $\mathrm{USp}(4)$ 1
893.a.893.1 893.a $$y^2 + (x^3 + x + 1)y = -x^4 - x^2$$ $\mathrm{USp}(4)$ 1
932.a.3728.1 932.a $$y^2 + y = x^6 - 2x^5 + x^4 + x^2 - x$$ $\mathrm{USp}(4)$ 1
953.a.953.1 953.a $$y^2 + (x^3 + x + 1)y = x^3 + x^2$$ $\mathrm{USp}(4)$ 1
961.a.961.1 961.a $$y^2 + (x^3 + x + 1)y = -x^6 - x^5 - 7x^4 + 74x^3 - 145x^2 + 99x - 33$$ $G_{3,3}$ 0
971.a.971.1 971.a $$y^2 + y = x^5 - 2x^3 + x$$ $\mathrm{USp}(4)$ 1
1051.a.1051.1 1051.a $$y^2 + y = x^5 - x^4 + x^2 - x$$ $\mathrm{USp}(4)$ 1
1077.b.1077.2 1077.b $$y^2 + y = x^5 + 14x^4 + 38x^3 - 79x^2 + 15x - 1$$ $\mathrm{USp}(4)$ 0
1083.b.390963.1 1083.b $$y^2 + y = -x^6 + 3x^5 - 50x^4 + 95x^3 - 14x^2 - 33x - 6$$ $G_{3,3}$ 0
1094.a.2188.1 1094.a $$y^2 + (x^3 + 1)y = x^4 - x^2$$ $\mathrm{USp}(4)$ 1
1109.a.1109.1 1109.a $$y^2 + y = x^5 - 6x^4 - 36x^3 - 6x^2 + 63x - 36$$ $\mathrm{USp}(4)$ 0
1127.a.1127.1 1127.a $$y^2 + (x^3 + x + 1)y = -x^4 + x^3 - x^2 - x$$ $\mathrm{USp}(4)$ 1
1198.a.2396.1 1198.a $$y^2 + (x^3 + 1)y = -x$$ $\mathrm{USp}(4)$ 1
1205.a.1205.1 1205.a $$y^2 + y = x^5 + 2x^4 - x^2$$ $\mathrm{USp}(4)$ 1
1207.a.1207.1 1207.a $$y^2 + (x^2 + x + 1)y = -x^5 - x^4$$ $\mathrm{USp}(4)$ 1
1253.a.1253.1 1253.a $$y^2 + (x^3 + x^2 + 1)y = -x^6 + 2x^5 - 33x^3 + 43x^2 + 15x - 330$$ $\mathrm{USp}(4)$ 0
1253.b.1253.1 1253.b $$y^2 + (x^3 + x + 1)y = x^4 + x^2$$ $\mathrm{USp}(4)$ 1
1269.a.1269.1 1269.a $$y^2 + (x^3 + x^2 + x + 1)y = x^2 + x$$ $\mathrm{USp}(4)$ 1
1327.a.1327.1 1327.a $$y^2 + (x^2 + x + 1)y = x^5 + 2x^4 + x^3$$ $\mathrm{USp}(4)$ 1
1343.a.1343.1 1343.a $$y^2 + (x^3 + x + 1)y = x^5 - 2x^4 - x$$ $\mathrm{USp}(4)$ 1
1343.b.1343.1 1343.b $$y^2 + (x^3 + x + 1)y = -3x^4 + x^3 + 2x^2 + x$$ $\mathrm{USp}(4)$ 1
1383.a.4149.1 1383.a $$y^2 + y = x^5 + x^4$$ $\mathrm{USp}(4)$ 1
1385.a.6925.1 1385.a $$y^2 + y = x^5 + 3x^4 + 3x^3 - x$$ $\mathrm{USp}(4)$ 1
1397.a.1397.1 1397.a $$y^2 + y = x^5 - x^3$$ $\mathrm{USp}(4)$ 1
1403.a.1403.1 1403.a $$y^2 + y = x^5 + x^4 - x^3 - x^2$$ $\mathrm{USp}(4)$ 1
1468.a.2936.1 1468.a $$y^2 + (x^3 + x + 1)y = -x^5 - x^2$$ $\mathrm{USp}(4)$ 1
1497.a.1497.1 1497.a $$y^2 + (x^3 + x + 1)y = -x^4 + x^3 - 2x^2 + x - 1$$ $\mathrm{USp}(4)$ 1
1497.b.13473.1 1497.b $$y^2 + (x^3 + x + 1)y = -2x^5 + 3x^4 - x^2$$ $\mathrm{USp}(4)$ 1
1499.a.1499.1 1499.a $$y^2 + (x^3 + 1)y = -x^5 + x^2 - x$$ $\mathrm{USp}(4)$ 1
1503.a.4509.1 1503.a $$y^2 + (x^3 + x + 1)y = x^5 - x^4 - 3x^3 + x$$ $\mathrm{USp}(4)$ 1
1519.a.1519.1 1519.a $$y^2 + (x^3 + x + 1)y = -2x^4 + 2x^2 - x - 1$$ $\mathrm{USp}(4)$ 1
1532.a.392192.1 1532.a $$y^2 + (x^2 + x + 1)y = x^5 + 7x^4 - 53x^2 + 12x - 1$$ $\mathrm{USp}(4)$ 0
1544.a.3088.1 1544.a $$y^2 + (x^3 + x^2 + x + 1)y = x^2$$ $\mathrm{USp}(4)$ 1
1549.a.1549.1 1549.a $$y^2 + (x^3 + x + 1)y = -x^5 + x^3 - 3x$$ $\mathrm{USp}(4)$ 1
1612.a.3224.1 1612.a $$y^2 + (x^3 + x + 1)y = x^3 + 2x^2 + x$$ $\mathrm{USp}(4)$ 1
1637.a.1637.1 1637.a $$y^2 + y = x^5 - x^4 + x^3 - x^2$$ $\mathrm{USp}(4)$ 1
1643.a.1643.1 1643.a $$y^2 + y = x^5 + x^4 - 5x^3 + 5x^2 - 2x$$ $\mathrm{USp}(4)$ 1
1647.a.1647.1 1647.a $$y^2 + (x^3 + x + 1)y = x^5$$ $\mathrm{USp}(4)$ 1
1701.a.1701.1 1701.a $$y^2 + y = x^5 + 19x^4 + 86x^3 - 60x^2 + 12x - 1$$ $\mathrm{USp}(4)$ 0
1706.a.3412.1 1706.a $$y^2 + (x + 1)y = x^6 - x^5 - x^4$$ $\mathrm{USp}(4)$ 1
1717.b.1717.1 1717.b $$y^2 + (x^3 + x)y = -x^4 - 2x^3 - 2x^2 - x$$ $\mathrm{USp}(4)$ 1
1721.a.1721.1 1721.a $$y^2 + (x^3 + 1)y = x^2 - x$$ $\mathrm{USp}(4)$ 1
1753.a.1753.1 1753.a $$y^2 + (x^3 + 1)y = x^2$$ $\mathrm{USp}(4)$ 1
1757.a.1757.1 1757.a $$y^2 + (x^3 + x^2 + x + 1)y = x^3 + x^2$$ $\mathrm{USp}(4)$ 1
1777.a.1777.1 1777.a $$y^2 + (x^3 + x + 1)y = -3x^4 + 7x^2 - x - 8$$ $\mathrm{USp}(4)$ 1
1797.a.5391.1 1797.a $$y^2 + (x^2 + x + 1)y = x^5 - 4x^4 + 2x^3 + x^2$$ $\mathrm{USp}(4)$ 1
Next